Juridical Analysis of Halal Certification as a Legal Obligation for MSMEs from the Perspective of Law No. 33 of 2014 and Maqashid Sharia: Juridical Analysis of Halal Certification as a Legal Obligation for MSMEs from the Perspective of Law No. 33 of 2014 and Maqashid Sharia - Fansuri, Hamzah (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to analyze the obligation of halal certification for Micro, Small, and Medium Enterprises (MSMEs) based on Law Number 33 of 2014 concerning Halal Product Assurance, as well as to examine its implementation from the perspective of maqashid sharia. The method used is normative juridical legal research with a statutory and maqashid sharia-based approach. The results of the study indicate that, normatively, halal certification constitutes a binding legal obligation and carries administrative sanctions for violations. However, its implementation in the field faces serious challenges, especially for MSME actors, in the form of cost, technical, and administrative constraints, as well as unequal access to facilities and information. From the perspective of maqashid sharia, this policy supports the realization of the objectives of Islamic law, such as the protection of religion (hifz al-din), life (hifz al-nafs), wealth (hifz al-mal), intellect (hifz al-‘aql), and progeny (hifz al-nasl). Nevertheless, a critical evaluation reveals that its implementation has not fully reflected the principles of justice and public benefit (maslahah) due to the absence of proportionate affirmative treatment for MSMEs. Therefore, a policy reformulation is needed that emphasizes educational and facilitative approaches, rather than solely coercive administrative measures. Halal certification should not only serve as a legal instrument but also as a means of economic empowerment aligned with the values of maqashid sharia.